New strategies and partnerships for the sustainable use of plant genetic resources - Vernooy, Ronnie; Halewood, Michael; López Noriega, Isabel; Galluzzi, Gea (Bioversity International, 2012)
Estimates suggest that globally 80% of the seeds on which smallholder farmers in developing countries depend are produced by the farmers themselves or obtained through informal channels. This high level of farmer seed autonomy masks the fact that almost everywhere local seed systems and the diverse agricultural production practices that depend on them are under some form of stress. Factors impacting on local seed systems include pests and diseases, loss of soil fertility and droughts and floods. Other factors include socio-economic and institutional forces, such as the inefficiency or absence of agricultural research and extension services, and formal seed systems that are unable to cater to the needs of smallholder farmers who depend on diversity and locally adapted cultivars. Although in many regions of the world farmers continue to try to maintain a diversity of crops and crop varieties, there are concerns that this diversity is declining in terms of both number of species and area sown or planted. These changes are taking place at a time when farmers are increasingly exposed to the impacts of climate change